The lunch of Círio of Our Lady of Nazaré in Belém, Pará, Brazil: cultural and gastronomic experience - Kato, Hellen Christina de Almeida (2020)
The “Círio” of Our Lady of Nazareth occurs more than two hundred years in Belem. The festival lasts fifteen days with religious and secular activities. In this article we will study the Círio’s lunch, considered and celebrated as the "Pará’s Christmas", in order to show their cultural and gastronomical features. The study is qualitative with an anthropological approach that used participant observation, in addition to bibliographic and documentary research. It is concluded that the characteristics that stand out most in this event are the traditionality of the dishes offered and the identity relationship that the people of Pará have with their food, in addition to the dualistic character (profane and religious) that permeates the festival and its activities.